2022
DOI: 10.2147/ndt.s359472
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Stigma Among University Students in Makkah: A Cross-Sectional Study

Abstract: Background Epilepsy is a neurological disorder characterized by a persistent propensity to generate recurring epileptic seizures. Young adults such as university students can bridge the gap and improve attitudes toward patients with epilepsy and reduce stigma. This study aims to assess the knowledge and attitude of university students in the city of Makkah about epilepsy. Methods This cross-sectional descriptive study was carried out at main universities in the Makkah r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This finding is consistent with previous studies that have reported a lack of knowledge among pharmacists regarding the association between valproic acid and the risk of autism in offspring. Unfortunately, various studies, including those conducted in the region, have shown that individuals with epilepsy face stigma and negative attitudes from both society and some healthcare professionals (38)(39)(40). Pharmacists can play a crucial role in educating patients, their families, and society about epilepsy and its associated health issues.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies that have reported a lack of knowledge among pharmacists regarding the association between valproic acid and the risk of autism in offspring. Unfortunately, various studies, including those conducted in the region, have shown that individuals with epilepsy face stigma and negative attitudes from both society and some healthcare professionals (38)(39)(40). Pharmacists can play a crucial role in educating patients, their families, and society about epilepsy and its associated health issues.…”
Section: Discussionmentioning
confidence: 99%